2012
DOI: 10.1102/1470-7330.2012.0003
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of diagnostic imaging technologies in breast cancer: discovery, regulatory approval, reimbursement, and adoption in clinical guidelines

Abstract: In this article, we trace the chronology of developments in breast imaging technologies that are used for diagnosis and staging of breast cancer, including mammography, ultrasonography, magnetic resonance imaging, computed tomography, and positron emission tomography. We explore factors that affected clinical acceptance and utilization of these technologies from discovery to clinical use, including milestones in peer-reviewed publication, US Food and Drug Administration approval, reimbursement by payers, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…In the long-term, it is likely that the most viable and applicable COU for blood-based biomarkers within the “diagnostic” realm is to serve as the first-step in a multi-stage diagnostic process where CSF and PET amyloid and tau imaging will serve as the final diagnostics of presence of AD pathology[5]. Given the cost of PET and CSF methods relative to blood-based methods, the availability of a blood-based tool in primary care settings that is utilized to determine who does and does not undergo PET and CSF exams has a viable cost and patient acceptability strategies, which are also the strategies followed in the cancer arena (i.e., PET scans are not first-line diagnostics[39]).…”
Section: Current State Of the Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In the long-term, it is likely that the most viable and applicable COU for blood-based biomarkers within the “diagnostic” realm is to serve as the first-step in a multi-stage diagnostic process where CSF and PET amyloid and tau imaging will serve as the final diagnostics of presence of AD pathology[5]. Given the cost of PET and CSF methods relative to blood-based methods, the availability of a blood-based tool in primary care settings that is utilized to determine who does and does not undergo PET and CSF exams has a viable cost and patient acceptability strategies, which are also the strategies followed in the cancer arena (i.e., PET scans are not first-line diagnostics[39]).…”
Section: Current State Of the Sciencementioning
confidence: 99%
“…As was the case with breast cancer screening 30-years ago, primary care screening tools are needed for AD though significant issues related to fear, stigma and misinformation remain[61]. Additionally, when considering the historical context of the emergence of diagnostic imaging technologies for breast cancer along with the regulatory and reimbursement approval patterns of those technologies[39], the availability of cost- and resource-effective strategies for staging the allocation of diagnostic resources in AD that fit within the existing medical infrastructure will increase the likelihood of regulatory approval for additional imaging modalities, as well as result in more rapid speed-to-market. It is important to be clear that, at this point, blood-based biomarkers are not viewed as “diagnostic”, but rather as the potential first-line in a multi-staged diagnostic process, because they are potentially more cost- and time-effective than other biomarker technologies, and may yield excellent accuracy when compared to primary care screening tools with similar COU[5].…”
Section: Placing Blood-based Biomarkers Into a Broader Contextmentioning
confidence: 99%
“…MRI of the breast was approved by the FDA as an adjunct to mammography for the detection of breast cancer in 1991. 35 Since that time, MRI of the breast has been further refined and is now considered the most sensitive imaging tool available for the diagnosis of invasive breast cancer. 36 Limitations of MRI of the breast must be weighed against the potential benefits when selecting candidates for screening MRI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…They found that use of new imaging technologies was driven mainly by regulatory approval and payment by health plans, "rather than evidence that they provide benefits to patients." 9 The trajectory of genetic testing appears poised to replay that of the growth of diagnostic imaging. Spending on genetic testing and molecular diagnostics is projected to reach $15-25 billion by 2021.…”
Section: Lessons Learned or "Déjà Vu All Over Again?"mentioning
confidence: 99%